MENGEMBALIKAN FUNGSI ILMU PENDIDIKAN ISLAM BAGI UMAT - Ira Suryani; Desy Kartika Dewi; Cindri Madelta; Aulia Asmidah HSB; Muhammad Iqbal Ritonga; Muhammad Aidi fahreza (STKIP Subang, 2023)
Family education is an important part of behavioral education. In general, family education is carried out through the introduction of religious and ethical values which include manners, customs and behavior that must be carried out in everyday life. The aim of this work is to show and discuss the role of Islamic religious education in the family and society. This writing method is a literature study with a descriptive and research approach. From this it can be concluded that the role of Islamic religious education is: (1) the foundation in the family to shape the behavior and morals of children and know the boundaries of good and bad, (2) form people who believe in Allah SWT and fear Him SWT, (3) the most important foundation and role. in moral education for the development of Indonesian society as a whole.